Fitoplâncton como indicadores de zonas estuarinas em sistema deltaico – Costa Equatorial do Atlântico Sul - OLIVEIRA, Amanda Lorena Lima (2019)
The Parnaíba River Delta is the only open ocean in the American continent with an area of 2,700 km2. The river is located in the Northeast of Brazil, being the second largest in width, discharge and size of the drainage basin. It presents a system of mesomarés, subject to the El Niño Southern Oscillation phenomenon. The objective work to investigate the phytoplankton community and to identify species indicative of estuarines influenced by local seasonality. To carry out the study were made analysis of physical and chemical variables, nutrients, chlorophyll a and density phytoplankton during 2018 considering the tide cycle (low tide and preamar) and periods (rainy, transition and drought), with a previous characterization physics of the estuary. From the obtained data it was verified a clear zonation of the estuary preamar, while at low tide the river flow dominates the system in the period rainfall, with salinities and temperatures typical of fluvial environments. The precipitation pluviometric changes the salinity gradient, nutrient concentrations, turbidity and MPS, reducing the availability of light that along with the entrance of the tide are factors determining the distribution of the community. As for the biological variables, the abundance was higher in the ZR (river zone) and chlorophyll a in the ZC (coastal zone). At species in the low-lying rainy season were Planktolyngbya liming, Strombomonas fluviatilis in ZR and Strombomonas sp. in the ZM (mixing zone). In preamar Chaetoceros lorenzianus and Coscinodiscus sp. typical of marine environment, stood out in ZC. In the transition period, Cyclotella meneghiniana, Cylindrotheca closterium, Coscinodiscus oculus-iridis and Chroococcus sp. species adapted to turbulent environments with water turbulence, characteristics of ZM and ZC. In the dry season, at low tide, we selected Staurastrum asteroideum, Pseudanabaena sp. Trachelomonas volvocina (ZR) and Trichodesmium erythraeum (ZC). Such results contribute to the knowledge of the conditioning factors in the determination of patterns spatial and temporal changes in this deltaic ecosystem with marked seasonal influence.